The Impact of War Conditions on Multidimensional Poverty and Development in Northwestern Syria: A Field Study of Idlib and Aleppo Governorates in 2024 - Taher, Ayaz Shukri; Al-Chikh Ali, Samir (Journal of Economic, Administrative and Legal Sciences, 2025)
This research examines the relationship between social development and multidimensional poverty in the northwestern governorates of Idlib and Aleppo, as a model case study for conflict zones and the impact of war on development. The research relies on recent studies and reports on measuring multidimensional poverty and applies the Oxford Community Initiative methodology to measure the Multidimensional Poverty Index (MPI), which is based on three dimensions: health, education, and standard of living. A social sample survey was conducted in the districts, sub-districts, villages, and camps of Idlib and Aleppo governorates, using a stratified random sample of 494 households and 2,568 individuals. The results showed a high poverty rate, reaching 25%, and that 47% of individuals suffer from extreme poverty and deprivation. Disparities in multidimensional poverty indicators were evident between cities, rural areas, and camps. Standard of living and education in the camps contributed more than 85% of multidimensional poverty, with approximately 31% of children not attending school, and approximately 43% of them did not complete primary education. There was a clear disparity in multidimensional poverty indicators between Idlib and Aleppo governorates, with the severity of deprivation being 5.5% higher in Aleppo than in Idlib. The percentage of children deprived of education in cities reached 60.7% and 50.8% in villages. Regarding health indicators, 10% suffered from acute malnutrition, and approximately 7% of households had under-five mortality. This percentage reached 11.2% in camps. Regarding standard of living indicators, more than 3% lacked electricity, rising to 5% in camps. Regarding access to clean drinking water, nearly 7% of households lacked it, with the percentage reaching 13.5% in rural areas and 20% in camps. Furthermore, approximately 7% of camp residents were deprived of cooking gas, and more than 17.7% lived in tents or mud houses lacking the most basic housing requirements.